Campus Carry and Constrained Behavior: faculty and Students’ Perceptual Responses to Campus Carry Laws - Noga-Styron, Krystal (Criminology, criminal justice, law & society, 2022)
Historically, policy discussions and decisions by lawmakers have failed to sufficiently consider the emotional and behavioral reactions of campus community members and how these reactions might shape the academic environment when crafting campus carry laws. Such considerations are especially relevant given the paucity of data on whether open carry laws reduce crime. The current study, which surveyed students, faculty, staff, and administrators at two Pacific Northwest universities (one in Oregon and another in Washington) during the 2016 - 2017 academic year, expands on past research to include variables that measure one’s position on campus and state context. This study also expands on past research that focused primarily on support or opposition to campus carry measures, to include a more nuanced look at what various members of the campus community perceive will be the consequences of campus carry measures. Findings show that both students and faculty perceive negative consequences of campus carry laws and that faculty members would constrain their behaviors more than students if campus carry were allowed. A discussion of control variables and the implications of these findings are explored.